Adjuvant antibiotic therapy in duodenal ulcers treated with colloidal bismuth subcitrate. Issue 9 (September 1990) - O'Riordan, T; Mathai, E; Tobin, E; McKenna, D; Keane, C; Sweeney, E; O'Morain, C
Abstract : Persistence of Helicobacter pylori after duodenal ulcer healing is associated with high rates of ulcer relapse. We compared colloidal bismuth subcitrate alone with CBS combined with one of four antibiotic regimens in the treatment of duodenal ulcers. Endoscopy and antral biopsies were performed before treatment and four weeks afterwards. Biopsy specimens were examined for histological evidence of gastritis and by Gram stain and culture for H pylori infection. Altogether 141 patients were allocated to one of five treatment groups. Giving CBS and metronidazole (400 mg tid for 7 days) with and without amoxycillin (500 mg tid) achieved higher clearance rates of H pylori than treatment with CBS alone (p less than 0.01). These two combinations also achieved higher rates of antral gastritis healing than CBS alone (p less than 0.01 and p less than 0.05 respectively). Susceptibility to metronidazole was tested in 29 isolates before and in seven isolates after treatment with metronidazole by disc diffusion test and minimum inhibitory concentration assay. Twenty seven (93%) of the isolates were sensitive before treatment while six of seven (86%) were resistant afterwards. Four of the six resistant strains had acquired resistance during treatment and one of these had acquired metronidazole resistance despite concomitant treatment with amoxycillin, to which it remained sensitive. CBS with adjuvant metronidazole at a dose of 400 mg tid for seven days significantly improves the eradication of H pylori compared with CBS alone. Acquired metronidazole resistance, however, seems to be an important cause of failure to eradicate H pylori.